Aids and tuberculosis: coinfection from the perspective of the quality of life of patients - Neves, Lis Aparecida de Souza; Canini, Sílvia Rita Marin; Reis, Renata Karina; Santos, Cláudia Benedita dos; Gir, Elucir (Revista da Escola de Enfermagem da USP, 2012)
Tuberculosis (TB) and HIV coinfection adversely affects the lives of individuals in both the biological and psychosocial aspects. Aiming to describe the quality of life of individuals with HIV/TB coinfection, this descriptive cross-sectional study was conducted in Ribeirão Preto-SP. Participants were HIV-seropositive individuals with and without TB, using the WHOQOL HIV BREF. 115 individuals who were HIV-positive participated: 57 were coinfected and 58 were not; most were male heterosexuals, predominantly aged 40-49 years. Of those coinfected, most had lower education and income. In assessing the quality of life the coinfected individuals showed lower results in all areas, with significant differences in the Physical, Psychological, Level of Independence and Social Relations areas. TB and HIV / AIDS are stigmatized diseases, and overlap of the two may have severe consequences on the physical and psychosocial health of the individual.